ENVIRONMENTAL CONCERN: DOES IT DRIVE GREEN PURCHASE INTENTION OF SUSTAINABLE PACKAGING? - Mongula, Angelline; Masnita, Yolanda; Kurniawati, Kurniawati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2023)
The growing importance of environmental concern as a critical issue has recently increased. Lower environmental damage raises consumer awareness of the importance of environmental preservation. Environmental concern triggers consumers"™ interest in purchasing products with sustainable packaging. This study aims to examine factors driving the green purchase intention of sustainable packaging. The Theory of Planned Behavior (TPB) was utilized to identify the green purchase intention with six antecedents: subjective norm, price consciousness, perceived consumer effectiveness, perceived social media marketing, environmental concern, and perceived behavioral control. The data was analyzed using Structural Equation Modeling (SEM). The results revealed that the perceived social media marketing activities are the most influential driver of the green purchase intention, followed by the perceived behavioral control. Further, this study found that the environmental concern stimulates the perceived consumer effectiveness. This research contributes to marketers, companies, and the government to target appropriate marketing activities and engage potential consumers in purchasing the products with sustainable packaging.JEL: M31, Q56.